Correction to: Towards a consensus definition of maternal sepsis: results of a systematic review and expert consultation - Mercedes Bonet; Vicky Nogueira Pileggi; Marcus J. Rijken; Arri Coomarasamy; David Lissauer; João Paulo Souza; Ahmet Metin Gülmezoglu (BMC, 2018)
Abstract After publication of the original article [1], it came to the authors' attention that the Acknowledgements section was not completed correctly. The Acknowledgements of the article should have been as follows.